2023
DOI: 10.1002/jmv.28621
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical efficacy and safety of molnupiravir for nonhospitalized and hospitalized patients with COVID‐19: A systematic review and meta‐analysis of randomized control trials

Abstract: The efficacy of molnupiravir in treating patients with coronavirus disease 2019 (COVID‐19) has been inconsistent across randomized controlled trials (RCTs). Thus, this meta‐analysis was conducted to clarify the literature. A literature search of electronic databases—PubMed, Embase, and Cochrane Library—was performed to identify relevant articles published up to December 31, 2022. Only RCTs that investigated the clinical efficacy and safety of molnupiravir for patients with COVID‐19 were included. The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The TriNetX platform enables the establishment of cohorts by developing inclusion and exclusion criteria, which can be matched to control for confounding variables, and outcomes of interest can be analyzed over specific timeframes. The data source is well‐established and has been used to study medical topics of global relevance, including the COVID‐19 pandemic 25–30 . As aggregated deidentified data were used, written informed consent was not required.…”
Section: Methodsmentioning
confidence: 99%
“…The TriNetX platform enables the establishment of cohorts by developing inclusion and exclusion criteria, which can be matched to control for confounding variables, and outcomes of interest can be analyzed over specific timeframes. The data source is well‐established and has been used to study medical topics of global relevance, including the COVID‐19 pandemic 25–30 . As aggregated deidentified data were used, written informed consent was not required.…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of adverse events was significantly higher in patients receiving molnupiravir compared to those receiving sotrovimab. Recently published meta‐analyses revealed that there was no significant difference in the incidence of adverse events between the molnupiravir and control groups 21,44,46 . Additionally, our previous research revealed no significant difference in the incidence of adverse events between different doses of molnupiravir (200, 400, and 800 mg) and placebo in COVID‐19 patients 48 .…”
Section: Discussionmentioning
confidence: 81%
“…Recently published metaanalyses revealed that there was no significant difference in the incidence of adverse events between the molnupiravir and control groups. 21,44,46 Additionally, our previous research revealed no significant difference in the incidence of adverse events between different doses of molnupiravir (200, 400, and 800 mg) and placebo in COVID-19 patients. 48 This discrepancy can be attributed to the type of control groups in the meta-analyses.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To the Editor, Huang et al 1 raised several concerns about our recent metaanalysis. 1 First, he thought that Caraco et al's study 2 was the interim analysis of the full MOVe-out study, 3 so it should not include interim and entire studies at the same time. In fact, MOVe-OUT was a phase 2/3 double-blind, parallel-group, randomized placebo-controlled trial.…”
mentioning
confidence: 99%